2017
DOI: 10.1038/cddis.2017.253
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR-128a induces Lin28a expression and reverts myeloid differentiation blockage in acute myeloid leukemia

Abstract: Lin28A is a highly conserved RNA-binding protein that concurs to control the balance between stemness and differentiation in several tissue lineages. Here, we report the role of miR-128a/Lin28A axis in blocking cell differentiation in acute myeloid leukemia (AML), a genetically heterogeneous disease characterized by abnormally controlled proliferation of myeloid progenitor cells accompanied by partial or total inability to undergo terminal differentiation. First, we found Lin28A underexpressed in blast cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Several lines of evidence have implicated that SBD exerts a strong activity of anti-tumour, anti-oxidative stress and anti-inflammation [10][11][12]. Recent studies mainly focused on its anti-tumour effects which have been reported in many kinds of cancers [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have implicated that SBD exerts a strong activity of anti-tumour, anti-oxidative stress and anti-inflammation [10][11][12]. Recent studies mainly focused on its anti-tumour effects which have been reported in many kinds of cancers [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Scutellaria barbata D. Don (SBD), also known as Ban-Zhi-Lian, is a perennial herb with multiple pharmacological effects, including anti-inflammation, anti-oxidation and anti-tumour activity [10][11][12]. It has been demonstrated that SBD has a strong inhibitory effect on numerous human cancers, such as lung cancer, hepatocellular carcinoma and skin cancer [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies demonstrated the existence of distinct miRNA profiles in different AML subtypes, indicating that miRNA signature contributed to AML heterogeneity, and suggesting its potential inclusion in clinical setting [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In Table 1 were reported all major studies comparing miRNA profile between AML blasts and normal cells, and among AML with recurrent genetic abnormalities [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Most of the reported studies exhibited high concordance in AML miRNA profile.…”
Section: Distinctive Pattern Of Mirnas In Amlmentioning
confidence: 99%
“…miR-181 and miR-128 target Lin28, leading to the progression of myeloid leukemia and differentiation blockage of hematopoietic cells to their lineage ( 15 , 70 , 71 ). The inhibition of miR-181 expression partially reverses the lack of myeloid differentiation in AML patients and in the mice implanted with CD34+ hematopoietic stem/progenitor cells (HSPCs) from AML patients ( 72 ).…”
Section: Emerging Roles Of Mirna Deregulation In the Pathogenesis Of mentioning
confidence: 99%